2023
DOI: 10.3389/fimmu.2023.1226057
|View full text |Cite
|
Sign up to set email alerts
|

E3 ubiquitin ligases and deubiquitinases in bladder cancer tumorigenesis and implications for immunotherapies

Abstract: With the rapidly increasing incidence of bladder cancer in China and worldwide, great efforts have been made to understand the detailed mechanism of bladder cancer tumorigenesis. Recently, the introduction of immune checkpoint inhibitor-based immunotherapy has changed the treatment strategy for bladder cancer, especially for advanced bladder cancer, and has improved the survival of patients. The ubiquitin–proteasome system, which affects many biological processes, plays an important role in bladder cancer. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 180 publications
0
3
0
Order By: Relevance
“…Not unlike most post-translational modification, ubiquitination is also associated with many cell functions, including cell cycle progression, apoptosis, gene transcription, DNA repair, and signal transduction, which regulate cell development and differentiation and tumorigenesis ( 35 , 36 ). Therefore, components in the ubiquitin pathway have been proposed as potential targets for treatment strategies for diseases and cancer ( 37 , 38 ). USP7 is one of the most abundant USPs and plays a multifaceted role in many cellular events, including carcinogenic pathways ( 39 - 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Not unlike most post-translational modification, ubiquitination is also associated with many cell functions, including cell cycle progression, apoptosis, gene transcription, DNA repair, and signal transduction, which regulate cell development and differentiation and tumorigenesis ( 35 , 36 ). Therefore, components in the ubiquitin pathway have been proposed as potential targets for treatment strategies for diseases and cancer ( 37 , 38 ). USP7 is one of the most abundant USPs and plays a multifaceted role in many cellular events, including carcinogenic pathways ( 39 - 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had already revealed the abnormal ubiquitination mechanisms of multiple onco-proteins or tumor suppressors during the development and progression of malignant tumors [ 30 32 ]. In bladder cancer, a variety of proteins were aberrantly expressed in tumors and functioned as E3 ubiquitin ligases, involved in the regulation of various biological processes including proliferation, invasion, cell cycle, apoptosis, stemness and chemoresistance [ 33 36 ]. For instance, the expression of TRIM38 was shown to be low in bladder cancer, and it was inversely associated with overall survival and advanced clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with non-muscle-invasive bladder cancer have a five-year overall survival of nearly 80% but are prone to a high rate of recurrence. Once the cancer has become muscle-invasive, the five-year survival rate drops to less than 40%, and once metastasized (stage T4), to less than 5% [ 2 ]. The treatment armamentarium has considerably grown in the last few years, including immune checkpoint inhibitors, targeted drugs and antibody–drug conjugates.…”
Section: Introductionmentioning
confidence: 99%